Infection control in general practices in Buffalo City and OR Tambo District Municipalities, South Africa - Don O'Mahony (AOSIS, 2012)
Background: Good infection control practices are effective in reducing rates of infection in health care settings. Studies in primary care in developed countries indicate that many general practitioners (GPs) do not comply with optimal infection control practices. There are no published studies from developing countries in Southern Africa. Objectives: The aim of this study was to describe infection control practices in private GP surgeries in the Buffalo City and OR Tambo District Municipalities in the Eastern Cape Province, South Africa. Method: A literature review was conducted to appraise current best practice with respect to Standard Infection Control and Transmission Based Precautions. A questionnaire, inquiring into GPs' actual practices, was posted to each surgery. Results: The valid response rate was 34% (47/140). Methods used to sterilise instruments in 40 practices were: ultraviolet sterilisation (23), chemical disinfection (14), boiling water (7), and steam autoclave (2). Compounds used for chemical disinfection included organotin quaternary, chlorhexidine and benzyl ammonium chloride with a quaternary complex. Twenty-two (47%) used a hand rub. Sixteen (35%) GPs stated that they had a policy to promptly triage patients who are coughing, and 23 (50%) had a policy for airflow movement in the surgery. All practices appropriately disposed of sharps. Thirty-seven (80%) expressed interest in a seminar on infection control. Conclusions: Overall, GPs were aware of infection control precautions. Ultraviolet sterilisers and chlorhexidine are not recommended, however, for sterilisation or high level disinfection of medical instruments, and their use should be discontinued. Hand rubs are underutilised. GPs should implement Transmission Based Precautions to prevent airborne and droplet infections.